QlikView unlocked : unlock more than 50 amazing tips and tricks to enhance your QlikView skills - Stone, Roger; Dove, Andrew (Professional expertise distilled., 2015)
Unlock more than 50 amazing tips and tricks to enhance your QlikView skills About This Book Learn QlikView development best practices from the experts Discover valuable tips, tricks, and undocumented features A fast-paced guide with techniques and best practices to optimize high-performance, robust, and scalable applications Who This Book Is For QlikView Unlocked is intended for anyone with at least some experience in designing, developing, or supporting QlikView applications. Whether you are new to QlikView or are a seasoned developer, there is something for everyone in this book. What You Will Learn Build the QlikView environment correctly so that it is flexible and robust Deliver a successful QlikView project Understand and implement QlikView best practices Discover the best way to prototype, develop, and deploy applications Overcome data modeling challenges Explore the in's and out's of Section Access Solve post-deployment issues in Server and Publisher In Detail QlikView is considered as one of the most used tool for Business Intelligence (BI). An efficient BI tool should provide five important capabilities for effective data analysis - collection (gathering important information), reporting, analysis (the ability to interact with data), visualization (the presentation of data), and discovery (exploring data). QlikView offers all these necessary skills required to deal with big data in real-world scenarios. QlikView Unlocked will provide you with new insights to get the very best from QlikView. This book will help you to develop skills to work with data efficiently. We will cover all the secrets of unleashing the full power of QlikView, which will enable you to make better use of the tool and create better results for future projects. In the course of this book, we will walk you through techniques and best practices that will enable you to be more productive. You will gain quick insights into the tool with the help of short steps called ?keys,? which will help you discover new features of QlikView. Moving on you will learn new techniques for data visualization, scripting, data modeling, and more. This book will then cover best practices to help you establish an efficient system with improved performance. We will also teach you some tricks that will help you speed up development processes, monitor data with dashboards, and so on. By the end of this book, you will have gained beneficial tips, tricks, and techniques to enhance the overall ex...